DAMPAK KETERBUKAAN PERDAGANGAN DAN KINERJA MANUFAKTUR DI INDONESIA - Wahyu Dyah Novitasari; Sri Hartoyo; Lukytawati Anggraeni (IPB University, 2015)
This study aims to analyze the impact of trade openness on the performance of manufacturing in Indonesia. In the study, performance and manufacturing growth indicated by the index of competitiveness and manufacturing added value. In aggregate, over the last few years, trade performance of Indonesia’s manufacturing sector has decreased due to the low index of competitiveness and comparative advantage. The empirical results using an Autoregressive Distributed Lag (ARDL) model with Error Correction Approach (ECM) shows that trade openness consistently negative effect on manufacturing value added, implicitly increase one percent change in trade openness would be deficit of changes in manufacturing value added of 4.26 billion rupiah, ceteris paribus. Furthermore, the amount of labor consistently positive effect on manufacturing value added, while fixed capital variable and value-added of previous lag (a year earlier) take effect by unstable in the long term as well as short then the crisis has also negatively affect the manufacturing value added.